Meningkatkan Keterampilan Berpikir Kritis Menggunakan Model Pembelajaran DIGEST Di Sekolah Dasar - Rizma Azizah; Novitawati . (CV. ITTC INDONESIA, 2024)
The problem in this research is the low critical thinking skills of students which of course has an impact on student learning outcomes in Civics content in class IV at SDN Benua Anyar 4 Banjarmasin. One effort to improve critical thinking skills and student learning outcomes is by implementing the DIGEST learning model which is a combination of the Problem Based Learning, Contextual Teaching and Learning, and Talking Stick models. The aim of this research is to describe teacher activities, analyze student activities and critical thinking skills related to student learning outcomes. This research used the Classroom Action Research method which was carried out in 3 meetings with 12 students consisting of 9 male students and 3 female students. The results of this research show that teacher’s activities at the first to third meetings continued to increase so that they obtained very good criteria. Then, student activity at the first to third meetings continued to increase so that all students were active. And also students critical thinking skills at the first to third meetings continued to improve so that all students achieved the criteria for being critical. Classical completeness of student learning outcomes at the first to third meetings also continues to increase so that it is achieved. Based on the results obtained, using the DIGEST model can improve teacher activity, student activity, student critical thinking skills, and student learning outcomes